UPAYA MENINGKATKAN KEMAMPUAN SISWA BERBAHASA INDONESIA MELALUI MODEL ROUND CLUB - Sondang Gultom (JURNAL GLOBAL EDUKASI, 2018)
Abstract: The purpose of this study is to improve students' ability to speak Indonesian well and correctly in environmental material through the Club round model. The subjects in this study were fifth grade students of SD Negeri 010142 Gonting Malaha district Island Bandar academic year 2017/2018. Based on the results of the study, it is known that students' ability to speak Indonesian properly and correctly through a round club model has increased in each cycle. The average result of the first cycle is 80.1 and the second cycle becomes 82.3. Learning outcomes in the first cycle reached classical completeness of 80.9% and in the second cycle to 100%. The students' keatifity in the first cycle was 55% and the second cycle was 86%. It can be concluded that the use of the round club learning model can improve students' ability to speak Indonesian well and correctly in the material environment in class V SD Negeri 010142 Gonting Malaha district Island Bandar academic year 2017/2018. Keywords: round club, speak Indonesian Abstrak: Tujuan penelitian ini adalah meningkatkan kemampuan siswa dalam berbahasa Indonesia dengan baik dan benar pada materi Lingkungan melalui model round Club. Subjek dalam penelitian ini adalah siswa kelas V SD Negeri 010142 Gonting Malaha kec. Bandar Pulau TP. 2017/2018. Berdasarkan hasil penelitian diketahui bahwa kemampuan siswa dalam berbahasa Indonesia dengan baik dan benar melalui model round club terjadi peningkatan pada tiap siklusnya. Hasil rata-rata siklus I sebesar 80,1 dan siklus II menjadi 82,3. Hasil belajar pada siklus I mencapai ketuntasan klasikal sebesar 80,9% dan pada siklus II menjadi 100%. Keatifan siswa pada siklus I sebesar 55% dan siklus II menjadi 86%. Dapat disimpulkan bahwa dengan penggunaan model pembelajaran round club dapat meningkatkan kemampuan siswa dalam berbahasa Indonesia dengan baik dan benar pada materi Lingkungan di kelas V SD Negeri 010142 Gonting Malaha kec. Bandar Pulau TP. 2017/2018. Kata kunci: round club, berbahasa Indonesia